Interest in Micellar Solution to Reduce Unpleasant Skin Sensations - Taieb C; Gayraud F; Dinet D; Sayag M (Dove Medical Press, 2021)
Charles Taieb,1 Floriane Gayraud,2 Delphine Dinet,2 Michele Sayag2 On behalf on the project "Ma Peau & Moi&#x201D1European Market Maintenance Assessment, Patients Priority Dpt, Fontenay sous-bois, France; 2NAOS, Research and Development, Lyon, FranceCorrespondence: Charles TaiebEuropean Market Maintenance Assessment, Patients Priority Dpt, Fontenay sous-bois, FranceEmail charles.taieb@emma.clinicIntroduction: The results from the "Objectifs Peau" project showed that approximately 30% of the French population complains of an unpleasant skin sensation at least once a day. Itching was the most frequent complaint (32%), followed by tingling (18.9%) and burning sensation (5.6%), which impact an individual's daily life. These sensations could be identified, as they were either isolated or associated with each other. The aim of this study was to evaluate the use of micellar solution to reduce these sensations, especially on sensitive skin.Methodology: A questionnaire was administered at Day 0 (D0), D2, D14, and D28 using a mobile phone application to individuals applying micellar solution (Sensibio H2O, Laboratoire Bioderma, NAOS) who spontaneously used micellar solution for sensitive skin and/or spontaneously consulted a health professional. Itching, tightness, tingling and burning sensations were evaluated by means of frequencies (never, rarely, sometimes, often or constantly) at D0, D2, D14 and D28. Responses from the questionnaire were rated (never=0, rarely=1, sometimes=2, often=3 or constantly=4) and allowed us to obtain an overall "unpleasant sensations" score, where a higher score corresponded to a higher degree of unpleasant sensations.Results: In total, 400 evaluable individuals participated in the study (97% female, average age 38.5± 13 years, 82% reported sensitive skin). The "unpleasant sensations" score improved from D2 and continued significantly on D14 and D28. The improvement rates were 47.7%, 57.9% and 62.7% at D2, D14 and D28, respectively, compared to D0. The percentages of improvement at D2, D14 and D28 were 83.2% (95% CI: 79.26; 87.21), 87.54% (95% CI: 84.01; 91.06) and 90% (95% CI: 87.06; 92.94), respectively, compared to D0.Conclusion: The improvement in the reduction of unpleasant sensations was observed as early as 2 days after using micellar solution and increased over time. The use of this type of micellar solution, especially on sensitive skin, and the guidance of health professionals (dermatologists and pharmacists) may help to reduce the impact of unpleasant skin sensations.Keywords: unpleasant skin sensations, micellar solution, patient centricity, itching, tightness, tingling, burning sensation